Connective Tissue Naevus - Bhat Ramesh M; Shetty J N; Raok Sudarshan (Wolters Kluwer Medknow Publications, 1999)
A young adult female patient of connective tissue naevus presented with papules and indurated plaques on both les and left arm. Histopathology showed increased amount of collagen in the dermis. Osteopoikilosis was absent.